The Effectiveness of The Combination of Nanoparticles from Carica papaya L. Leaf and Chitosan 1% Against Fibroblasts in The Tooth Socket of Wistar Rats. - Sim, Mellisa; Helen Theresia Nauli; Dang Phuong Khanh; Novelya; Felice Florencia Nicoline (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Nanoparticles size can make easier for drugs to enter and react quickly to the body.In this study, nanoparticles Carica papaya L. leaf were used and combined withchitosan 1%. The aim of this study was to measure the effectiveness of thecombination of nanoparticles from Carica papaya L. leaf and chitosan 1% againstfibroblasts in the tooth socket of Wistar rats. Carica papaya L. leaf extract wasmade by maceration method and converted into a concentration of 25%, 50%, 75%and 100%, then made into nanoparticles using the nanoemulsion method. Chitosan1% was made using Na-TPP solvent using the ionic gelation method with a ratio of2:1 and after that it was mixed with nanoparticles of Carica papaya L. leaf thenmade into a gel preparation. The ANOVA statistical test shows a significant numberof p <0.05, so it can be ignored that the increase in the number of fibroblast cellsproduced by the nano gel extract is 25%, 50%, 75% and 100%, its 138, 173, 177.4and 328. Thus, the combination of 100% Carica papaya L. leaf nanoparticle extractand 1% nanocitosan was the most effective in increasing fibroblast cells on Wistarrat tooth socket.